(untitled) (Economics and region, 2022)
The article is devoted to topical issues of functioning of the labor market of Ukraine under martial law. The number of vacancies and unemployed is analyzed and systematized. The areas of employment that are most in need of workers according to the State Employment Service and those that are least in demand are considered. The top 10 key "soft skills" in vacancies offered by employers in pre-war and wartime are outlined. The average offered salary and the percentage of its decrease in May 2022 compared to the pre-war period are investigated. The main factors of changes in the structure of labor supply in Ukraine in the post-war period are determined. The necessary measures of social policy of post-war reconstruction are proposed. Obtaining up-to-date information on trends in the labour market in a country where there is a war, the number and composition of the workforce is changing, is a difficult task, given that even with the outflow of several million able-bodied refugees, unemployment in Ukraine remains high. Despite the revival of economic activity and the gradual return of enterprises to work, many enterprises have not resumed their activities, and this affects the labor market. According to the International Labor Organization of the United Nations, many qualified specialists of our country are currently looking for work. The number of vacancies has decreased even in the IT sector, despite the fact that this sphere was perhaps the most prepared for the war, and employees are mobile and flexible. The labor market began to belong to employers, and due to falling revenues, many of them resorted to layoffs and salary cuts. Stabilization of the labour market in the post-war period is an extremely important task, given the emergence of different groups of the population affected by the armed conflict, in particular internally displaced persons, including children and women, people with disabilities and ex-combatants. The specific needs of these groups should be taken into account when planning and implementing sustainable reintegration processes, including in the area of employment. It is important to develop an effective system of labor market management (mechanisms and tools for its implementation), taking into account the issues of education, development of special skills, as well as improving social protection and security.